Prevalence of patellar tendinopathy and patellar tendon abnormality in male collegiate basketball players: A cross-sectional study - Hutchison, M. K.; Houck, J.; Cuddeford, T.; Dorociak, R.; Brumitt, J. (Journal of Athletic Training, 2019)
Context Patellar tendinopathy (PT) is a degenerative condition known to affect athletes who participate in sports such as basketball and volleyball. Patellar tendinopathy is a challenging condition to treat and may cause an athlete to prematurely retire from sport. The prevalence of PT in male collegiate basketball players is unknown.